2014
DOI: 10.1051/0004-6361/201323337
|View full text |Cite
|
Sign up to set email alerts
|

INTEGRAL andSwiftobservations of the hard X-ray transient MAXI J1828-249

Abstract: In this paper we report on the observations performed with INTEGRAL and Swift of the first outburst detected from the hard X-ray transient MAXI J1828-249. During the first about two days of the outburst, the source was observed by MAXI to undergo a very rapid transition from a hard to a softer spectral state. While the hard state was not efficiently monitored because the transition occurred so rapidly, the evolution of the source outburst in the softer state was covered quasi-simultaneously in a broad energy r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…This is reminiscent of that of MAXI J1836−194, which exhibited an incomplete state transition and never reached the high/soft state. Considering all the above results, and presuming that the hysteresis is observed only after the source completed its hard-to-soft state transition, we infer that MAXI J1828−249 stayed in the soft intermediate state and did not reach the genuine high/soft state in the Suzaku observation, as also suggested by Filippova et al (2014). The observed properties of MAXI J1828−249, including the strong hard tail and relatively enhanced variability above ∼ 5 keV, are literally between those in the low/hard state and the high/soft state (table 3).…”
Section: Identification Of the Spectral Statesupporting
confidence: 60%
See 1 more Smart Citation
“…This is reminiscent of that of MAXI J1836−194, which exhibited an incomplete state transition and never reached the high/soft state. Considering all the above results, and presuming that the hysteresis is observed only after the source completed its hard-to-soft state transition, we infer that MAXI J1828−249 stayed in the soft intermediate state and did not reach the genuine high/soft state in the Suzaku observation, as also suggested by Filippova et al (2014). The observed properties of MAXI J1828−249, including the strong hard tail and relatively enhanced variability above ∼ 5 keV, are literally between those in the low/hard state and the high/soft state (table 3).…”
Section: Identification Of the Spectral Statesupporting
confidence: 60%
“…It is hence suggested that the source was evolving through the low/hard state toward the high/soft state, even though a transition to the genuine high/soft state was not clearly recognized. X-ray spectra obtained in this period were characterized with a strong multi-color disk blackbody component and a power-law tail with a photon index of ∼2, seen mainly below and above ∼10 keV, respectively (Filippova et al 2014;Grebenev et al 2016). Then, the flux gradually decreased for ∼100 days down to undetectable levels.…”
Section: Long-term X-ray Evolution In the Outburstmentioning
confidence: 90%
“…During the first two days of the outburst, the source was observed by MAXI to undergo a very rapid transition from a hard to a softer state [348], so that observations of the source in the LHS were limited because of the swiftness of the transition. The rest of the outburst (essentially the HSS) was covered by a joint observation campaign over a wide energy range from 0.6-150 keV by the instruments on Swift and INTEGRAL, although MAXI J1828−249 did not show significant spectral evolution [130], reaching, however, a peak luminosity L ≈ 10 38 ergs s −1 assuming a distance of 8 kpc.…”
Section: Maxi J1828−249mentioning
confidence: 99%
“…When fitting the broadband spectra, we added the cross-calibration constants between the three instruments to take into account the nonsimultaneity of the observations. A difference of the cross-calibration constants between the JEM-X and ISGRI/IBIS instruments is observed when working with the INTEGRAL data (see, e.g., Filippova et al 2014a).…”
Section: Integral Datamentioning
confidence: 99%
“…It is believed that during an outburst the system must pass from the low/hard to high/soft state and back, exhibiting the intermediate states and a characteristic "q" shape on the hardness-intensity diagram (Belloni and Motta 2016). However, many sources with black hole candidates exhibit the so-called failed outbursts, when the system does not reach the high/soft state (Ferrigno et al 2012(Ferrigno et al , 2014aDel Santo et al 2015; Mereminskiy et al 2017).…”
Section: Introductionmentioning
confidence: 99%